The Role of Lactobacillus plantarum in Enhancing the Physical Quality and pH of Water Hyacinth (Eichhornia crassipes) Silage - Agustina Widyasworo Kunharjanti; Agung Setya Wibowo; Muhammad Aldi Zulkarnain (Universitas Islam Balitar, 2025)
This research investigated the impact of supplementing water hyacinth (Eichhornia crassipes) silage with Lactiplantibacillus plantarum on its physical properties (pH, odor, texture, color, and fungal growth) as well as palatability. A Completely Randomized Design (CRD) was employed with three treatments and six replications: P0 (control, no L. plantarum), P1 (L. plantarum at 10⁵ CFU/ml), and P2 (L. plantarum at 10⁶ CFU/ml). The variables measured were pH, color, aroma, texture, fungal presence, and palatability. Findings revealed that L. plantarum supplementation significantly influenced (p < 0.05) the color of the silage, but had no significant effect on pH, aroma, texture, fungal development, or palatability. The mean pH values for P1 and P2 were 4.1 and 4.2, respectively, compared with 4.0 in P0. In terms of palatability, P2 produced the highest intake (201.5 g), followed by P1 (118.6 g), whereas P0 showed minimal consumption. Overall, the results suggest that higher concentrations of L. plantarum improve the visual quality of water hyacinth silage, but provide limited enhancement of other physical attributes and palatability.